Florid osseous dysplasia with chronic suppurative osteomyelitis in Asian female: an incidental finding on Panoramic and CBCT examination - Sukmadewi, Putri Marina; Pramanik, Farina (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: In a previous case study, we reported an incidental finding of florid osseous dysplasia with osteomyelitis, which was identified on panoramic and CBCT imaging. Case Report: A 53-year-old female patient came to the Radiology Department of Dental Hospital Padjadjaran Bandung with the chief complaint of recurrent pain one year ago; there was swelling from the cheek to the left mandible; the swelling reappeared one week ago with clinical pus mixed with blood in the swelling area. The patient had previously seen an oral surgeon and was referred for panoramic and CBCT radiographs. The results of the panoramic radiographs were that there was an irregular radiopaque lesion with ill-defined borders in the posterior region affecting 4 quadrants; in the sinister mandibular region, there was cortical destruction, root resorption, and the lesion appeared to extend to the canalis mandibular area. The CBCT examination showed multiple globular radiopaque lesions affecting 4 quadrants in the posterior area. There were sequestra with lytic lesions on the sinistra mandible resulting in buccal and lingual cortical bone discontinuity and buccal-lingual expansion. Expansion of the lesion area resulted in discontinuity of the canals mandibular sinistra and decreased bone density of the trabeculae up to the mandibular ramus; there was apical resorption trabecula bone density. From the Panoramic examination and CBCT results, the suspect radiodiagnosis was Florid osseous dysplasia associated with osteomyelitis. Conclusion: An examination of panoramic and CBCT images revealed FOD that had been secondarily infected with chronic diffuse osteomyelitis.